A novel patient‐specific three‐dimensional drug delivery construct for regenerative endodontics. Issue 5 (3rd October 2018) - Bottino, Marco C.; Albuquerque, Maria T. P.; Azabi, Asma; Münchow, Eliseu A.; Spolnik, Kenneth J.; Nör, Jacques E.; Edwards, Paul C.
Abstract: Evoked bleeding (EB) clinical procedure, comprising a disinfection step followed by periapical tissue laceration to induce the ingrowth of undifferentiated stem cells from the periodontal ligament and alveolar bone, is currently the only regenerative‐based therapeutic approach to treating pulp tissue necrosis in undeveloped (immature) permanent teeth approved in the United States. Yet, the disinfection step using antibiotic‐based pastes leads to cytotoxic, warranting a biocompatible strategy to promote root canal disinfection with no or minimal side‐effects to maximize the regenerative outcomes. The purpose of this investigation was to develop a tubular three‐dimensional (3D) triple antibiotic‐eluting construct for intracanal drug delivery. Morphological (scanning electron microscopy), chemical (Fourier transform infrared spectroscopy), and mechanical (tensile testing) characteristics of the polydioxanone‐based triple antibiotic‐eluting fibers were assessed. The antimicrobial properties of the tubular 3D constructs were determined in vitro and in vivo using an infected ( Actinomyces naeslundii ) dentin tooth slice model and a canine method of periapical disease, respectively. The in vitro data indicated significant antimicrobial activity and the ability to eliminate bacterial biofilm inside dentinal tubules. In vivo histological findings demonstrated that, using the EB procedure, the tubular 3D triple antibiotic‐eluting construct allowed the formation of an appropriate environment that led to apex closure and the ingrowth of a thin layer of osteodentin‐like tissue into the root canal. Taken together, these findings indicate that our novel drug delivery construct is a promising biocompatible disinfection strategy for immature permanent teeth with necrotic pulps. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1576–1586, 2019.